CSR in the Fast Moving Consumer Goods Retail Industry of Brunei Darussalam and its Influence on Supply Chain Management - Mohd Suria, Siti Fatimah Masayu (2008)
This dissertation is on the subject of corporate social responsibility (CSR), specifically looking at CSR in one of Brunei Darussalam's industries, to shed some light on the state of CSR in the country. The Fast moving Consumer Goods (FMCG) retail industry is chosen and three of the largest local firms are involve in the study. The main objective of the study is to find out the extent of CSR in these companies and to see if CSR has permeated into their supply chain management. A qualitative methodology is utilised for this purpose. Carroll's (1979) conceptualization and Moon's (2004) types of CSR waves are the theoretical frameworks used to guide analysis. Findings show differing extents of CSR engagement among these three companies, and that these are dependent on several factors including the national business system. Also, there is no proof of substantial CSR implementation in the supply chain management. It is concluded that in Brunei or in the FMCG retail industry at least CSR is not an established concept and is yet to be properly applied to supply chain management.